Oceanic Travels: Future Voyages for Moving Deep and Wide within the ''New Mobilities Paradigm''. Issue 2 (1st June 2019) - Peters, Kimberley; Squire, Rachael
Abstract : The seas and oceans, ships and boats, alongside other maritime activities and practices, have become a focus of work within the "new mobilities paradigm." However, water worlds much like the space they occupy in the relation to the land remain situated in the margins of such work, despite an oceanic (re)turn in disciplines such as human geography, sociology, anthropology, and politics. Drawing from this recognition, this article seeks to make two contributions. First, following earlier, agenda-setting work, it makes a renewed call for mobilities scholarship to centralize work on oceans, ships, and other forms seagoing travel and life. Second, in doing so, it suggests such work needs to voyage more deeply and widely in the future, exploring mobilities beyond surficial connections and flows across our oceans, and making more expansive the subjects and objects and scales of investigation, under the remit of the "new mobilities paradigm."